Using a crime prevention framework to evaluate tiger counter-poaching in a Southeast Asian rainforest - Lam, Wai Yee; Phung, Chee-Chean; Mat, Zainal Abidin; Jamaluddin, Hamidi; Sivayogam, Charina Pria; Zainal Abidin, Fauzul Azim; Sulaiman, Azlan; Cheok, Melynda Ka Yi; Osama, Noor Alif Wira; Sabaan, Salman; Abu Hashim, Abdul Kadir; Booton, Mark Daniel; et al. (Frontiers in Conservation Science, 2023)
Several tiger populations across their range are at risk of local extinction due to continued demand for their body parts and are reliant on strong site protection. Detecting and preventing tiger poaching at a site poses substantial challenges to the rangers responsible for protecting them. This is acute in Southeast Asia, where protected areas are often large, mountainous tropical forests with small ranger teams. Efforts to improve tactics are hampered by an absence of robust evaluations, perpetuating ineffective and expensive approaches. Here, we evaluate the success of a project aiming to increase tiger numbers by 50% by 2024 in the Kenyir Core Area in Terengganu, northeast Peninsular Malaysia. Using a framework developed to evaluate crime prevention known by the acronym EMMIE, we: (1) examine evidence on whether our counter-poaching operations were Effective in recovering tigers; (2) resolve the Mechanisms through which our counter-poaching operations cause a reduction in harm from poaching and the conditions that Moderate effectiveness; and (3) collate information on the Implementation and Economic costs of counter-tiger poaching operations. Our results suggest improvements in three stages of counter-poaching operations increased certainty of arrest in all poaching types. However, evidence that this dissuaded poachers from attempting an incursion is only supported for one group. While snares detected inside Kenyir increased due to tactical shift in poaching operations, rangers seized an increasing percentage of snares before they could be set, and deactivated live snares, reducing potential harm to tigers and prey. This enabled several resident female tigers to survive multiple years until two years of COVID-19 travel restrictions caused a near-total cessation of poaching. By 2021, the population density of tigers had stabilised close to the 2014 baseline, with leopards, sun bears and wild boars showing similar marginal recoveries from declines in the 2017 survey. Our study offers an example for teams with similar problems and landscapes in the region to conduct robust evaluations of their wildlife protection strategies and disentangle causality.